Recent developments on zinc(ii) metal–organic framework nanocarriers for physiological pH-responsive drug delivery. Issue 12 (17th October 2019) - Liu, Weicong; Pan, Ying; Xiao, Weiwei; Xu, Hongjia; Liu, Dong; Ren, Fei; Peng, Xinsheng; Liu, Jianqiang
Abstract : In this review article, we discuss the diverse stimuli achieved upon outside activation from single pH-stimulus-responsive or/and multiple pH-stimuli-responsive viewpoints in the body. Abstract : The high storage capacities and excellent biocompatibilities of zinc(ii ) metal–organic frameworks (Zn-MOFs) have made them outstanding candidates as drug delivery carriers. Recent studies on the pH-responsive processes based on carrier–drug interactions have proven them to be the most efficient and effective way to control the release profiles of drugs. To satisfy the ever-growing demand in cancer therapy, great efforts are being devoted to the development of methods to precisely control drug release and achieve targeted use of an active substance at the right time and place. In this review article, we discuss the diverse stimuli based on Zn-MOFs carriers that have been achieved upon external activation from single pH-stimulus-responsive or/and multiple pH-stimuli-responsive viewpoints. Also, the perspectives and future challenges in this type of carrier system are discussed.